IMPACT OF 10 SESSIONS OF WHOLE BODY CRYOSTIMULATION ON AEROBIC AND ANAEROBIC CAPACITY AND ON SELECTED BLOOD COUNT PARAMETERS - Tomasz Dybek; Renata Szyguła; Andrzej Klimek; Sławomir Tubek (Termedia Publishing House, 2012)
The systemic effect of low temperature suggests that sessions in a cryogenic chamber might improve athletes' capacity as a standard element of training. Therefore the authors decided to evaluate the impact of 10 sessions of whole body cryostimulation (WBCT) on aerobic and anaerobic efficiency as well as on selected blood count parameters. The study group included 32 volunteers - 16 women and 16 men. The volunteers underwent 10 sessions of WBCT in a cryogenic chamber. Blood samples (RBC, WBC, PLT, HGB, HCT) were taken, and aerobic and anaerobic efficiency and lactate concentration in capillary blood were measured before the first session and one day after the last one. No significant differences were observed in values of aerobic capacity after 10 sessions of WBCT. There was a rising trend in men and a declining trend in women. The lactate concentration did not differ significantly before and after WBCT. A slight rise in aerobic and anaerobic threshold was observed in men, while in women the values slightly fell. The Wingate test showed no significant differences in results before and after cryostimulation. Only the TOBT was significantly shorter in men (6.12±1.49 vs 3.79±1.14 s). The WBCT sessions resulted in a significant rise of the haematological parameters both in women and men, excluding HCT, which showed a statistically insignificant rise. Ten sessions of whole body cryostimulation did not affect aerobic or anaerobic capacity in the tested group, although it improved the blood count parameters.